Wear mechanisms identification using Kelvin probe force microscopy in TiN, ZrN and TiN/ZrN hard ceramic multilayers coatings. Issue 15 (15th October 2020) - González-Carmona, J.M.; Triviño, J.D.; Gómez-Ovalle, Á.; Ortega, C.; Alvarado-Orozco, J.M.; Sánchez-Sthepa, H.; Avila, A.
Abstract: Mechanical and tribological properties of titanium nitride, zirconium nitride, and (TiN/ZrN)n multilayers were studied to examine the potential of Kelvin probe force microscopy (KPFM) to identify wear mechanisms. Crystalline structure, chemical composition, residual stress, and the mechanical properties showed that the coatings are iso-structural polycrystalline multilayers, with a reduction of grain size, crystallite size, and compressive stress; however, hardness increased with increase in the number of the bilayers. Pin-on-disc test was used for tribological evaluation, and wear tracks were analyzed using field-emission scanning electron microscopy/energy dispersed spectroscopy (FE-SEM/EDS) and KPFM. The increase in mechanical properties generated predominantly abrasive wear mechanisms. Abrasive and adhesive wear mechanisms differentiated by KPFM demonstrated that fragile wear mechanisms presented differences in capacitance and surface potential and that the method is sensitive when the adhered material presents differences in chemical composition. We have demonstrated KPFM to be a promising technique to study tribo-oxidation processes, providing experimental evidence to understand the wear mechanisms at nanometric scales.